2010
DOI: 10.2174/187152810793938017
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Inflammation, Platelet Activation and Antiplatelet Resistance

Abstract: Even though there is a strong evidence suggestive of benefits and safety of dual (aspirin plus clopidogrel) antiplatelet therapy, decreased responsiveness or "resistance" to mono- and/or dual antiplatelet therapy has been described in association with an increased thrombotic risk. Various mechanisms contribute to antiplatelet resistance, with abundant production of inflammatory markers being of particular importance. The current review overviews implications of inflammation in antiplatelet resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 107 publications
0
7
0
2
Order By: Relevance
“…The above‐mentioned trials included patients with early onset STEMI and thrombus burden grade of 1‐3, which might have influenced the results, by showing a non‐significant additive value of TA compared with conventional PPCI . Prior studies have shown a strong association between older thrombus and worse outcomes with PPCI in patients with STEMI, which could be related to prolonged inflammation, increase in platelet activation and anti‐platelet resistance as well as distal coronary emboli with balloon inflation and stenting . Hence, the lack of clear benefit from TA in early STEMI presenters may not hold true for late presenters.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The above‐mentioned trials included patients with early onset STEMI and thrombus burden grade of 1‐3, which might have influenced the results, by showing a non‐significant additive value of TA compared with conventional PPCI . Prior studies have shown a strong association between older thrombus and worse outcomes with PPCI in patients with STEMI, which could be related to prolonged inflammation, increase in platelet activation and anti‐platelet resistance as well as distal coronary emboli with balloon inflation and stenting . Hence, the lack of clear benefit from TA in early STEMI presenters may not hold true for late presenters.…”
Section: Discussionmentioning
confidence: 59%
“…8,9 Prior studies have shown a strong association between older thrombus and worse outcomes with PPCI in patients with STEMI, which could be related to prolonged inflammation, increase in platelet activation and antiplatelet resistance as well as distal coronary emboli with balloon inflation and stenting. 6,7,21,22 Hence, the lack of clear benefit from TA in early STEMI presenters may not hold true for late presenters.…”
Section: Discussionmentioning
confidence: 99%
“…If the inflammatory stimulus is a lacerating wound, exuded platelets can help clot the wounded area and provide hemostasis 46 . All clotting mediators, including platelets, coagulants, plasmin, and kinins, provide a structural staging framework at the inflammatory tissue site in the form of a fibrin lattice for the purpose of aiding phagocytic debridement and wound repair 47 . In addition to “first responders” in wounds, platelets can also serve as “first responders” in cancer and metastasis 48 .…”
Section: Inflammation-involved Molecules and Immune Cellsmentioning
confidence: 99%
“…O acúmulo de plaquetas é um dos primeiros eventos na formação de trombo arterial e componente crítico da formação da placa de ateroma. As plaquetas estão presentes no sangue em número aproximado de 150-400x10 6 /mL e possuem vida média de 8 a 10 dias 3 . Além do seu papel nos processos de homeostase e trombose, as plaquetas também podem participar do reparo tecidual 4 , da inflamação 3 , da angiogênese 5 , do crescimento tumoral e da metástase 4,5 .…”
Section: Introdução 11 Plaquetasunclassified
“…Apesar de serem anucleadas as plaquetas possuem estrutura funcional complexa contendo organelas comuns aos outros tipos celulares tais como mitocôndrias, complexo de Golgi, ribossomos, peroxissomos e microtúbulos 6 . Ainda, as plaquetas possuem em seu citoplasma três tipos de grânulos classificados como denso, alfa e lisossomais 7 .…”
Section: Introdução 11 Plaquetasunclassified